Generalist or Specialist? On Dichotomies in the Educational Discourse. An Essay - Reichenbach, Roland (Swiss Journal of Educational Research, 2022)
The motivation behind the considerations are the rather less reasonable grounds on which the distinction between general and special education is made – seemingly “in a conceptual manner.” The phenomenal world is not divided into general objects on the one side and special objects on the other. This (conceptual-)analytical division, which is surely able to prove its cognitive function, misleads to the less plausible opinion that the amalgam of education and the educational process may be divided into its aspects. In the face of the social, political, economic, legal, but also individual-biographic and esthetic consequences or effects of such divisions and the thinking habits connected to them, there is an educational philosophy demand to question faintly reflected lacks of alternatives.